Novel C‐arm‐based planning robotic spinal surgery in a cadaver model using quantitative accuracy assessment methodology. Issue 6 (23rd August 2022) - Park, Sangman; Kim, Hyung Cheol; Jeong, Yeongha; Kim, Dongyun; Ryu, Seungjae; Lee, Seongpung; Cha, Yongyeob; Hwang, Sungteac; Woo, Donggi; Kim, Hongho; Shin, Dong Ah; Ha, Yoon; et al.
Abstract: Background: This preclinical study emulating the clinical environment quantitatively analysed the accuracy of pedicle screw insertion using a navigated robotic system. Methods: Pedicle screws were placed from T7 to L5 in the whole‐body form of a cadaver. After the insertion of multiple artificial markers into each vertebra, errors between the planned insertion path and the inserted screw were quantified using the Gertzbein‐Robbins system (GRS) and offset calculation. Results: A total of 22 screws were placed. Almost all (95.45% [21/22]) were classified as GRS A or B, while one (4.55%) was GRS C. The mean and standard deviations of entry, tip, and angular offset were 1.78 ± 0.94 mm, 2.30 ± 1.01 mm, and 2.64 ± 1.05°, respectively. Conclusions: This study demonstrated that pedicle screw insertion using a navigated robotic system had high accuracy and safety. A future clinical study is necessary to validate our findings.